ANALYSIS OF WORKING CAPITAL MANAGEMEN AND ITS EFFECT ON FIRM PROFITABILITY - Klemens Mere (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Working capital management (WCM) involves the control and optimization of a company’s current assets and liabilities, such as inventory, accounts receivable, accounts payable, and cash balances. It plays a vital role in a firm’s liquidity, operational efficiency, and financial health. The purpose of this study is to analyze working capital management and its effect on firm profitability. This literature review has examined the relationship between working capital management (WCM) and firm profitability by synthesizing findings from various empirical and conceptual studies. The evidence consistently indicates that effective WCM plays a critical role in enhancing a firm’s financial performance.